Reforming Economic Mechanisms in Leading Strategic Enterprises of Uzbekistan: Reformasi Mekanisme Ekonomi di Perusahaan Strategis Utama Uzbekistan - Umarova Irodakhon Nuraliyevna (Academia Open, 2025)
General Background: Large enterprises in strategic sectors are pivotal for national economic growth, employment, and innovation. Specific Background: In Uzbekistan, despite ongoing reforms aimed at liberalization, privatization, and digital integration, these enterprises continue to rely on outdated, bureaucratic management models. Knowledge Gap: Existing global and local research offers valuable theoretical frameworks, but lacks practical applicability to Uzbekistan’s unique economic and sectoral characteristics, particularly in terms of digital readiness and human capital constraints. Aims: This study aims to develop a comprehensive and adaptable model for improving economic management mechanisms in dominant enterprises, integrating strategic planning, digital transformation, and resource optimization. Results: Empirical analysis revealed that sectors with advanced ERP and BI adoption, such as telecom and energy, achieved over 12% cost savings and up to 90% forecast accuracy. Conversely, sectors like agriculture and textiles lagged due to poor digital infrastructure. Novelty: The study combines benchmarking, sectoral data, and interdisciplinary insights to propose context-sensitive reforms, emphasizing digital systems integration, strategic flexibility, and corporate independence. Implications: The proposed model underscores the necessity of multidimensional reform-balancing economic efficiency, state policy alignment, and human capital development—to ensure sustainable, market-oriented enterprise transformation. Highlights: Modernization Imperative. Traditional bureaucratic management systems in large Uzbek enterprises are ineffective; intelligent, digital-compatible systems are urgently needed. Digital and Human Capacity Gaps. Digital transformation is uneven across sectors; lack of skilled personnel hinders ERP/BI implementation and financial planning. Policy and Responsibility Shift. Enterprise transformation should be aligned with national policy, emphasizing corporate independence, innovation, and social responsibility. Keywords: Economic Mechanisms, Strategic Enterprises, Digital Transformation, Corporate Governance, Human Capital